Decentralization viewed from inside: the implementation of community forests in East Cameroon - Etoungou, P. (World Resources Institute, 2003)
Cameroon's 1994 Forestry law launched a new approach to natural resource management. The 1996 Constitution introduced decentralized authorities, whose role is to enable the economic, social and cultural development of its peoples. The new legal framework for environmental policy and overhaul of the Constitution show the Government's will to decentralize and to improve forest resources management. At the same time, decentralization management might be inappropriate in Cameroon. This study examines the community forests of East Cameroon to analyse factors that have not yet been fully taken into account in the current process of community forests establishment. These include exorbitant technical, financial and human costs; the ambiguous role of some international and local NGOs; the virtual, rather than substantial, Common Initiative Groups (CIGs) and Associations; and the disregard for traditional law, despite its legal primacy in African States. The interest in decentralization and forest management, also tied to the "development" of forest populations, has lead to a web of misunderstandings. These findings suggest the question: are community forests the best alternative for decentralized management in East Cameroon?